A thermodynamic approach to obtaining transparent spinel (MgAl2O4) by hot pressing. Issue 2 (February 2015) - Esposito, Laura; Piancastelli, Andreana; Miceli, Patrizia; Martelli, Stefano
Abstract Hot pressing has been investigated as a method for producing highly transparent, cost-effective MgAl2O4 for optical applications. The hot pressing of stoichiometric Al2O3–MgO powder mixtures has been preferred to the direct pressing of spinel powders, given the ready availability of pure powders and the opportunity to exploit the thermodynamic driving force for spinel formation. Ultra-pure LiF has been used as a sintering additive. An accurate thermodynamic study on the reactions involved in spinel formation has shed light on the mechanisms affecting the material's transparency, particularly as concerns the presence of a carbonaceous environment. Transparencies up to 70% in the visible range (maximum 78%) have been obtained. The present study focused on the pressure applied during sintering as one of the main parameters influencing the material's final optical properties.